Weight lifting technology biomechanics rapid feed back system study - Gao, Z.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Weightlifting is one of the important part of the Olympic. For a variety of reasons, the coach is by observation and experience qualitative methods on, the athletes technical action guide to further reveal the characteristics of technical action. The hope to be able to the test the qualitative and quantitative test of real combination more looking forward to the kinematics and dynamics of the key indicators. So after consulting a large number of literature and coaches discussion, we make the sports biomechanics research weight lifting technology rapid diagnosis system, the use of 3rd load station acquisition lower limb legal date, combining synchronous acquisition. Barbell center kinematics parameters to rapid analysis weightlifting action techniques. Help improve weightlifting athletes technical effect.